The Influence of Work Environment and Compensation on Employee Job Satisfaction at CV. Amanda Brownies Makassar - Edwin, Muhammad Farid Saputra; Ruma, Zainal; Dipoatmodjo, Tenri S. P. (Jurnal Riset Bisnis, Manajemen, dan Ilmu Ekonomi, 2024)
This study aims to examine the effect of physical work environment, non-physical work environment, financial compensation and non-financial compensation on employee job satisfaction at CV. Amanda Brownies. The population in this study were 74 respondents and used as a sample consisting of validity, reliability, normality, heteroscedasticity, multicollinearity, partial test, simultaneous test and determination coefficient test. The data used is quantitative data with multiple regression analysis tools using the SPSS Version 26 data processing application. The test results show that the physical work environment, non-physical work environment, financial compensation and non-financial compensation have a positive and significant effect on job satisfaction. Physical work environment, non-physical work environment, financial compensation and non-financial compensation simultaneously have a positive and significant effect on job satisfaction.